Nanostructured phase boundaries in aluminum under severe cyclic plastic deformation - Panin V. E. Viktor Evgenyevich; Surikova N. S.; Elsukova T. F.; Egorushkin V. E.; Pochivalov Yu. I. (2010, 2010)
The mechanisms of plastic strain observed at high degrees of alternating bending of thin aluminum foils glued to elastically strained substrates have been investigated. As extrusion and intrusion develop on the surface of the aluminum foils, multiscale fragmentation of the structure is found to take place in the bulk of the materials to form nanostructured phase boundaries between subgrains. The width of the phase boundaries varies between 200 and 300 nm, with the size of the structure elements within the subgrain boundaries being 30-50 nm. Formation of the nanostructured phase boundaries between nonequilibrium subgrains is regarded to be the fragmentation mechanism operative at the submicrometer scale level in the foils subjected to bending-torsion at very high degrees of plastic strain